Discrete-time impulsive Hopfield neural networks with finite distributed delays - Akҫa Haydar; Alassar, Rajai; Covachev, Valery; Yurtsever, H. Ali (Computer Assisted Methods in Engineering and Science, 2007)
The discrete counterpart of a class of Hopfield neural networks with periodic impulses and finite distributed delays is introduced. A sufficient condition for the existence and global exponential stability of a unique periodic solution of the discrete system considered is obtained.